2013
DOI: 10.1039/c3sm50814e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the gelation performance of melamine and 2-ethylhexylphosphoric acid mono-2-ethylhexyl ester in water–organic mixtures

Abstract: A two-component gel of melamine (M) and 2-ethylhexylphosphoric acid mono-2-ethylhexyl ester (P) in binary solvent mixtures has been investigated. PM formed opaque gels at a certain water volume fraction in methanol-water mixtures. The minimum gelation concentration (MGC) decreased with increasing the water content, whereas the gel-to-sol transition temperature (T gel ) increased firstly and had a decline at 60% water content. Scanning electron microscopy (SEM) images revealed that the gel fibers formed macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…4 However, the mechanisms governing the self-assembly of a number of supramolecular nanostructures, including supramolecular gels, are poorly understood. [14][15][16][17] Even though we can see from the already published results that the self-assembly process is inuenced by the factors mentioned above, very few studies have attempted to gain a more comprehensive analysis from combining the inuencing factors, including the solubility parameters, structures and generations on the selfassembly mechanism. The majority of these study a variety of structurally diverse molecules 8 and generations 9,10 to understand how the individual dendritic molecules are assembled into more complex arrays via non-covalent interactions and to explain the inuence of the gelator structure and generation on the selfassembling processes; 11-13 and a few of which attempt to gain a quantitative insight into the precise ways in which solvents inuence self-assembly and gelation.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, the mechanisms governing the self-assembly of a number of supramolecular nanostructures, including supramolecular gels, are poorly understood. [14][15][16][17] Even though we can see from the already published results that the self-assembly process is inuenced by the factors mentioned above, very few studies have attempted to gain a more comprehensive analysis from combining the inuencing factors, including the solubility parameters, structures and generations on the selfassembly mechanism. The majority of these study a variety of structurally diverse molecules 8 and generations 9,10 to understand how the individual dendritic molecules are assembled into more complex arrays via non-covalent interactions and to explain the inuence of the gelator structure and generation on the selfassembling processes; 11-13 and a few of which attempt to gain a quantitative insight into the precise ways in which solvents inuence self-assembly and gelation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fan et al reported a heating-cooling method that places two-component mixture of melamine and 2-ethylhexylphosphoric acid mono-2-ethylhexyl ester in a sealed glass tube with solvent and heats the solution until the solid dissolved, and the subsequent cooling of the solution at room temperature affords a hydrogel. 35 Liu et al demonstrated that precipitates or hydrogels formed depending on the molar ratios between glutamic acid based bolaamphiphile racemates and melamine when they heated and cooled the mixtures. 33 The change of the temperature probably is the most straightforward method for generating hydrogels from thermally stable heterotypic hydrogelators.…”
Section: Methods For Hydrogelationmentioning
confidence: 99%
“…The authors also found that the addition of organic solvent could tune the morphologies of the assemblies. 35 Tantishaiyakul and Dokmaisrijan et al used various experimental and computational techniques to investigate the heterotypical hydrogel formed by 6 and three positional isomer of aminobenzoic acid (AB). 30 Based on the rheological measurement, para-aminobenzoic acid (pAB)/ 6 gel is the strongest one due to the strong hydrogen bonding between 6 and pAB.…”
Section: Heterotypic Supramolecular Hydrogelsmentioning
confidence: 99%
“…(4-Benzyloxy-7-comarin)phenylacetylene (10). Thionyl chloride (SOCl 2 ) was added dropwise to a stirred solution of 4-ethinyl benzyl alcohol (8) (500 mg, 3.79 mmol) in dry dichloromethane with a few drops of DMF performing as catalysts at room temperature for 5 h to obtain compound 4-ethinyl benzyl chloride (9). A mixture of 4-ethinyl benzyl chloride (9) (550 mg, 3.65 mmol), 7-hydroxycoumarin (500 mg, 3.04 mmol) and anhydrous K 2 CO 3 (630 mg, 4.57 mmol) in dry DMF were stirred for 6 h at 70e80 C to afford 10 by etherification.…”
Section: Synthesismentioning
confidence: 99%
“…8 Niu et al reported that the change of gel property can be easily realized by simply changing the properties of solvents. 9 Hansen solubility parameters are widely used to predict compatibility between two materials. 10 Undoubtedly, it also can be used to predict the compatibility between solvent and gelator.…”
Section: Introductionmentioning
confidence: 99%